SUSTAINABILITY OF PIG FARMING BUSINESS DEVELOPMENT IN URBAN COMMUNITIES IN AMBON CITY, MALUKU PROVINCE - Tatipikalawan, Jomima Martha; Ririmasse, P.M.; Matatula, M.J.; Liur, Isye.J. (Fakultas Pertanian, Universitas Janabadra, 2024)
The purpose of this study is to analyze the index and sustainability status of pig farming business in urban communities in Ambon City and sensitive indicators affecting the sustainability of development in terms of ecological, socio-cultural, economic, technological and institutional dimensions. The research was conducted in Ambon City in 3 sub-districts (Baguala, Teluk Ambon, Nusaniwe). Data analysis using Rap-BABI ordination techniques through the Multi Dimensional Scaling (MDS) method to measure sustainability indices and status, Laverage Analysis to determine sensitive indicators, Monte Carlo analysis to assess the effect of errors on estimating the value of sustainability ordination of pig farming businesses. The results of the analysis found that the sustainability index of pig farming in Ambon City was 50.87% (sustainable). The results of the analysis of the sustainability index of pig farming in Ambon City are 50.87% (sustainable). Sustainability index per dimension: ecological 48.54% (less sustainable), socio-cultural 43.08% (less sustainable), economic 66.65% (sustainable), technology 45.69% (less sustainable), institutional 40.39% (less sustainable). Leverage analysis found 15 attributes that are sensitive and influential for the increase in sustainability indices so that they need to be interfered with various policies and strategies.Key Words: pig, Sustainability, dimension, Atrribute